2000
DOI: 10.1128/cdli.7.4.607-611.2000
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunosorbent Assays Using the Recombinant Dense Granule Antigens GRA6 and GRA1 of Toxoplasma gondii for Detection of Immunoglobulin G Antibodies

Abstract: The potential of the dense granule antigens GRA1 and GRA6 of Toxoplasma gondii to be used as diagnosis reagents in a recombinant form was evaluated. Both proteins were expressed in Escherichia coli as glutathione-S-transferase (GST) fusions. The GST-GRA1 fusion comprises the entire GRA1 sequence devoid of its N-terminal signal peptide. Separate expression of the two N-and C-terminal hydrophilic regions of GRA6 showed that only the N-terminal hydrophilic part of the protein was recognized by a pool of positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 16 publications
1
35
0
1
Order By: Relevance
“…Recent studies revealed that choosing recombinant chimeric multiepitope antigens (54,55) was instrumental in improving the performance of commercialized enzyme immunoassay kits in detecting T. gondii-specific antibodies, using either soluble antigens from crude extracts or recombinant antigens (56)(57)(58). The selection of the reagent that allows for both IgG and IgM detection should take into account the assay's performance under both routine conditions and specified clinical settings (such as high sensitivity for IgM in pregnancy and for IgG in immunosuppressed patients).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that choosing recombinant chimeric multiepitope antigens (54,55) was instrumental in improving the performance of commercialized enzyme immunoassay kits in detecting T. gondii-specific antibodies, using either soluble antigens from crude extracts or recombinant antigens (56)(57)(58). The selection of the reagent that allows for both IgG and IgM detection should take into account the assay's performance under both routine conditions and specified clinical settings (such as high sensitivity for IgM in pregnancy and for IgG in immunosuppressed patients).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data demonstrated the potential of using two or three complementary recombinant antigens in order to reach a sensitivity comparable to that obtained with a crude antigen preparation. In 2000, Lecordier et al (42) showed that the sensitivity of IgG ELISAs with the single recombinant antigens GRA1 and GRA6-Nt was low (68% and 96%, respectively). They also found that comparison of the optical density values for each serum sample revealed that GRA1 may complement GRA6-Nt to reach an overall sensitivity of 98%.…”
Section: The Mixture Of Recombinant Proteinsmentioning
confidence: 99%
“…Many of these recombinant antigens have been used for the detection of T. gondii-specific antibodies in human serum samples (38). Furthermore, several previous studies have found that recombinant antigens improve the serological diagnosis of toxoplasmosis (15,25,34,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). However, it is not only the improvement of T. gondii diagnosis with the use of recombinant antigens that is very important but, also, improvement in differentiating between the acute and chronic phase of toxoplasmosis.…”
Section: T Gondii Recombinant Antigensmentioning
confidence: 99%
“…The use of an Escherichia coli recombinant antigen(s) would be greatly beneficial in improving standardization of the tests and reducing their production costs. Thus, recent advances in generating recombinant antigens of T. gondii for IgG and IgM serological tests have been made (10,12,13,17,19,32). However, in contrast to the case for the current serological tests, none of these recombinant antigens has allowed detection of all serologically positive individuals.…”
mentioning
confidence: 99%